Structural brain differences in professional Australian rules footballers following mild traumatic brain injury: When head size matters - Lee, Jackson M.; Pardoe, Heath R.; Parker, Donna M.; Pedersen, Mangor; Makdissi, Michael; Abbott, David F.; Jackson, Graeme D.; Mito, Remika (Frontiers in Neurology, 2026)
IntroductionConcussion, a type of mild traumatic brain injury common in collision sports, is thought to be associated with subtle brain changes that are not visually appreciable on conventional neuroimaging. This study quantified differences in subcortical volumes from structural MRI between 31 recently concussed professional Australian rules footballers (within 3 months of injury) and 37 healthy, non-athlete controls.MethodsT1-weighted MRI were acquired at 3 T and processed using FreeSurfer. Hippocampal and amygdala volumes were normalized by estimated total intracranial volume (eTIV). Longitudinal changes were assessed in a subset of 12 footballers with follow-up MRI. Cortical thickness differences were also explored using vertex-wise analysis.ResultsFootballers exhibited lower proportional hippocampal and amygdala volumes, and reduced cortical thickness compared to controls. However, after exploring different methodological approaches for estimating intracranial volume (ICV), volumetric findings were seen to vary based on the ICV estimation method used for normalization.DiscussionThis study demonstrates subtle, likely persistent neuroanatomical differences between professional Australian rules footballers and non-athlete controls. Importantly, we advocate for cautious clinical interpretation of volumetric MRI findings considering methodological variabilities, particularly when inherent cohort differences (such as ICV) may bias results, and provide recommendations for future studies that examine volumetric changes in concussion cohorts.